Cybersecurity crisis management and lessons learned from the Covid-19 pandemic - Abassi, Ryma, 1980-; Ben Chehida Douss, Aida, 1986- (Advances in information security, privacy, and ethics (AISPE) book series., 2022)
"The COVID-19 pandemic has forced organizations and individuals to embrace new practices such as social distancing and remote working forcing a new focus on cybersecurity, and this book covers new research results, challenges and issues to be considered as the world is more digitally connected"--